2022
DOI: 10.3390/diagnostics12112599
|View full text |Cite
|
Sign up to set email alerts
|

Can Peri-Implant Marginal Bone Loss Progression and a-MMP-8 Be Considered Indicators of the Subsequent Onset of Peri-Implantitis? A 5-Year Study

Abstract: The aim of this retrospective study was to investigate the relationship between the amount of early bone remodeling, the marginal bone loss (MBL) progression, and the peri-implant sulcular fluid concentration of active metalloproteinase-8 (a-MMP-8) and the incidence of peri-implantitis (P) over 5 years of implant function. It has been documented that dental implants with a high degree of early marginal bone loss (MBL) are likely to achieve additional increased MBL during function. Moreover, it has been specula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Contradictory data are present in the literature about the influence of tissue phenotype on the onset of P [14,[55][56][57]. In the current study, the absence of a band of keratinized mucosa >2 mm was found to be a risk factor/indicator for P, but the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 66%
“…Contradictory data are present in the literature about the influence of tissue phenotype on the onset of P [14,[55][56][57]. In the current study, the absence of a band of keratinized mucosa >2 mm was found to be a risk factor/indicator for P, but the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 66%
“…In future studies, the use of reactive nitrogen species such as dinitrogen trioxide may be useful. The stimulus in this regard is also continuously provided by the enormous possibility offered by the currently available tests in the planning and analysis of interleukins and inflammatory factors present in the saliva and at the level of the crevicular fluid present in the implant and periodontal sulcus ( 19 - 22 ). Furthermore, it is essential to consider the long-term importance in the primary prevention of carious lesions in order to obtain greater safety margins, particularly in the treatment of orthodontic patients undergoing fixed therapy, with devices that risk predisposing to the onset of caries ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regenerated tissues play a crucial role in achieving stable, long-term implant rehabilitation, enhancing bone remodeling, and minimizing factors such as early marginal bone loss and inflammation. 5,6 Different regenerative methods can be used for alveolar ridge or bone reconstructions, ranging from minor augmentations with bone or bone substitute particles to extensive reconstructions with microsurgical free flaps. 7,8 A variety of surgical techniques and biomaterials are employed in alveolar reconstructive surgery.…”
Section: Introductionmentioning
confidence: 99%